KAJIAN PRODUKSI MINUMAN CAMPURAN SARI WORTEL DENGAN BERBAGAI BUAH - Ikrar Triastuti; Fibra Nurainy; Otik Nawansih (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
This research was aimed to find the most preferred fruitto be mixed with carrot juice, to determine the formulation ofcarrot and the chosen fruit that give the best mixed juice, andto elucidate the physical and chemical characteristics of thechosen juice stored at 10°C for 6 days. The fruits to be chosenwere pineapple, orange, red guava, mango, passion fruit. Theformulations carrot and the chosen fruit used were 50%: 50%,60%: 40%, 70%: 30%, 80%: 20%, 90%, 10%, and 100%: 0%.The results showed that the most preferred fruit to be mixedwith carrot was soursop. Selected formula that gave the bestsensory properties was 80% carrot : 20% soursop. This mixedjuice had scores for aroma, taste, color, and overall acceptanceof 3 (like slightly), 3.600 (like), and 3.240 (like slightly) .During 6- days of cold storage there was a slight decrease invitamin C, total soluble solid, and cloud stability, but there wasa slight increase in pH.Keywords: carrot, cloud stability, mixed juice, soursoup